Laser reprogramming magnetic anisotropy in soft composites for reconfigurable 3D shaping - Heng Deng (Nature Portfolio, 2020)
Responsive soft materials which can exhibit various three-dimensional (3D) shapes under the same stimulus are desirable for applications in adaptive and reconfigurable soft robots. Here, the authors report a laser rewritable magnetic composite film, whose responsive shape-morphing behaviors induced by a magnetic field can be digitally and repeatedly reprogrammed by a facile method of direct laser writing.